Analysis of the Design Space and Dexterity of a Planar Two Degree of Freedom Parallel Manipulator - Wang Bing; Nie Xumeng; Han Shukui (Jixie chuandong)
A novel planar two degree of freedom parallel manipulator is presented,its moving platform of the manipulator has smaller inertia and the output of the manipulator is planar translational motion.Unlike the traditional optimum analysis method,not only the geometric parameters,but also the range of the linear actuators of the manipulator are considered as the kinematics parameters,the design space is obtained by normalizing the actuation and geometric parameter.The dexterity performance index is calculated in the design space,the dexterity atlas of the manipulator is plotted.The dexterity atlas reflects the relationship between the dexterity performance index and the kinematics parameters of the manipulator.The dexterity atlas is very useful for the design of the new manipulator and the new method also provides a simple,comprehensive and effective way for design parallel manipulator that is actuated by linear actuators.